The therapeutic effect of adipose-derived lipoaspirate cells in femoral head necrosis by improving angiogenesis - Zhang, Weixin; Zheng, Cheng; Yu, Tiefeng; Zhang, Houjian; Huang, Jiaxin; Chen, Liyue; Tong, Peijian; Zhen, Gehua (Frontiers in Cell and Developmental Biology, 2022)
Femoral head necrosis (FHN), one of the most popular joint diseases in the musculoskeletal system, is usually attributed to local ischemia of the femoral head. Thus, regenerating the vascularization capacity and restoring the local perfusion of the femoral head becomes an efficient therapeutic approach for FHN. In the present study, we investigated the effect of autologous lipoaspirate cells (LPCs) in regenerating circulation in FHN animal models and human subjects. We also explored the mechanisms of why LPCs show a superior effect than that of the bone marrow-derived stem cells (BMSCs) in vascularization. Thirty-four FHN patients were recruited for the randomized clinical trial. Harris Hip Score (HHS) and digital subtraction arteriography (DSA) and interventional technique were used to compare the efficacy of LPCs treatment and vehicle therapy in improving femoral head circulation and hip joint function. Cellular mechanism that underlies the beneficial effect of LPCs in restoring blood supply and rescuing bone architecture was further explored using canine and mouse FHN animal models. We found that LPCs perfusion via the medial circumflex artery can significantly promote the vascularization and bone structure of the femoral head in both FHN patients and animal models. The HHS in LPCs treated patients was significantly improved relative to vehicle group. The levels of angiogenesis factor secreted by LPCs such as VEGF, FGF2, VEC, TGF-β, were significantly higher than that of BMSCs. As the result, LPCs showed a better effect in promoting the tube structure formation of human vascular endothelial cells (HUVEC) than that of BMSCs. Moreover, LPCs contains a unique CD44+CD34+CD31- population. The CD44+CD34+CD31- LPCs showed significantly higher angiogenesis potential as compared to that of BMSCs. Taken together, our results show that LPCs possess a superior vascularization capacity in both autonomous and paracrine manner, indicating that autologous LPCs perfusion via the medial circumflex artery is an effective therapy for FHN.